Characterization of National Immunization Programs in the Context of Public Health Emergencies: A Case Study of 13 Countries in the WHO Africa Region - Chepkurui, Viola; Amponsah-Dacosta, Edina; Haddison, Eposi Christiana; Kagina, Benjamin Mugo (Frontiers in Public Health, 2021)
Multiple public health emergencies (PHEs) experienced annually in the World Health Organisation (WHO) Africa region affect the provision of health services, including immunization. However, there is limited information on the performance of national immunization programs (NIPs) in WHO Africa countries that experience PHEs. This study assessed PHEs (armed conflicts, disasters, and disease outbreaks) and the performance of NIPs using global and regional immunization targets outlined for the Decade of Vaccines. Thirteen beneficiary countries of PHE mitigation funds from the African Public Health Emergency Fund were used as case studies. Data on PHEs and immunization indicators between 2010 and 2019 in selected countries were extracted from different PHE databases and the WHO/UNICEF immunization database, respectively. The data were stratified by country and summarized using descriptive statistics. Mann-Whitney U test was done to determine the association between the frequency of PHEs and the performance of NIPs. There were 175 disease outbreaks, 288 armed conflicts, and 318 disasters in the examined countries between 2010 and 2019. The Democratic Republic of Congo had the highest total PHE count (n = 208), while Liberia had the lowest (n = 20). Only three of the 13 countries had a median coverage value for the third dose of the combined Diphtheria, Tetanus, and Pertussis vaccine (DTP3) that had attained the target for ≥90% immunization coverage. Higher counts of armed conflict and total PHEs were associated with not meeting immunization targets for national DTP3 coverage of ≥90% and Maternal and Neonatal Tetanus elimination, p < 0.01. It was clear that in the WHO Africa region, PHEs are prevalent, irrespective of a country’s level of immunization maturity, and have the potential to derail the progress of NIPs in the absence of effective interventions. As we transition toward the Immunization Agenda 2030, we recommend that the WHO Africa region prioritizes interventions to mitigate the impacts of PHEs on NIPs.